High-level and reusable preparation of sulforaphane by yeast cells expressing myrosinase - Lili Wang; Hamed I. Hamouda; Yueyang Dong; Hong Jiang; Yongyi Quan; Yimiao Chen; Yan Liu; Jiaqi Wang; Mohamed A. Balah; Xiangzhao Mao (Food Chemistry: X, 2023)
Myrosinase is a key tool for the fast and efficient preparation of sulforaphane which is one of the prominent natural ingredients found in brassicaceous vegetables. Here, the glucoraphanin-hydrolyzing activity of a Yarrowia lipolytica 20–8 harboring myrosinase reached 73.28 U/g dry cell weight, indicating that it had a potential application in sulforaphane preparation from glucoraphanin. An efficient and reusable process for sulforaphane preparation via myrosinase produced by Y. lipolytica 20–8 was constructed. In detail, as high as 10.32 mg sulforaphane could be produced from 1 g broccoli seed under the reaction of 40 U yeast whole-cell catalyst within 15 min with the conversion efficiency of 99.86%. Moreover, when the yeast whole-cell catalyst was reused 7 and 10 times, as high as 92.53% and 87.56% of sulforaphene yield of the initial level could be retained, respectively. Therefore, this yeast whole-cell is a potent biocatalyst for the efficient and reusable preparation of sulforaphane.